2018
DOI: 10.1002/ps.4889
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance mutations of Pro197, Asp376 and Trp574 on the characteristics of acetohydroxyacid synthase (AHAS) isozymes

Abstract: The AHAS resistance mutations conferred D. sophia resistance to tribenuron-methyl by decreasing the binding affinity for tribenuron-methyl and/or increasing the binding affinity for pyruvate, but the mutations did not necessarily affect the biosynthesis of BCAAs in plants. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 48 publications
4
24
0
Order By: Relevance
“…Mutations in genes encoding both 5-enolpyruvylshikimate-3-phosphate synthase and acetyl-CoA carboxylase (ACCase) can reduce activity of the corresponding enzymes ( Healy-Fried et al , 2007 ; Yu et al , 2007 ; Vila-Aiub et al , 2015 b ). However, the situation in ALS is more complex, with specific amino acid substitutions causing reduced, increased, or unchanged enzyme activity in different weed species ( Boutsalis et al , 1999 ; Preston et al , 2006 ; Ashigh and Tardif, 2007 ; Yu et al , 2010 ; Vercellino et al , 2018 ; Yang et al , 2018 ). A case-by-case analysis is thus required to investigate the precise impact of specific gene modifications on ALS kinetics and the fitness of resistant versus susceptible plants.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in genes encoding both 5-enolpyruvylshikimate-3-phosphate synthase and acetyl-CoA carboxylase (ACCase) can reduce activity of the corresponding enzymes ( Healy-Fried et al , 2007 ; Yu et al , 2007 ; Vila-Aiub et al , 2015 b ). However, the situation in ALS is more complex, with specific amino acid substitutions causing reduced, increased, or unchanged enzyme activity in different weed species ( Boutsalis et al , 1999 ; Preston et al , 2006 ; Ashigh and Tardif, 2007 ; Yu et al , 2010 ; Vercellino et al , 2018 ; Yang et al , 2018 ). A case-by-case analysis is thus required to investigate the precise impact of specific gene modifications on ALS kinetics and the fitness of resistant versus susceptible plants.…”
Section: Introductionmentioning
confidence: 99%
“…ALS mutation diversity has been confirmed in many ALS inhibitor–resistant weeds. For example, amino acid substitution at Pro-197, Asp-376, and Trp-574 were found in D. sophia (Yang et al 2018a), kochia [ Bassia scoparia (L.) A. J. Scott] (Warwick et al 2008), and wild mustard ( Sinapis arvensis L.) (Warwick et al 2005; Whaley et al 2007); Ala-122, Pro-197, Asp-376, and Trp-574 mutations were identified in wild radish ( Raphanus raphanistrum L.) (Han et al 2012; Yu et al 2012); and Ala-122, Pro-197, Ala-205, Asp-376, Trp-574, and Ser-653 mutations were observed in redroot pigweed ( Amaranthus retroflexus L.) (Chen et al 2015; Huang et al 2016; McNaughton et al 2005). In this study, the molecular basis of ALS mutations has been well studied, and five different ALS mutations (Pro-197-Ser/Leu/His, Asp-376, and Trp-574) were established in tribenuron-methyl–resistant G. aprine .…”
Section: Resultsmentioning
confidence: 99%
“…Several works found that specific AHAS activity, kinetic parameters and/or feedback inhibition by the branched-chain amino acids were increased, decreased, and unchanged for different amino acid substitutions. [11][12][13] A previous study in wild sunflower showed no differences between AHAS extracted from resistant and susceptible biotypes. 7 Nonetheless, the impact of mutations on AHAS activity in cultivated sunflower is still unknown.…”
Section: Introductionmentioning
confidence: 89%
“…These resistance‐conferring mutations at AHAS may cause changes on enzyme functionality and varies widely among species. Several works found that specific AHAS activity, kinetic parameters and/or feedback inhibition by the branched‐chain amino acids were increased, decreased, and unchanged for different amino acid substitutions . A previous study in wild sunflower showed no differences between AHAS extracted from resistant and susceptible biotypes .…”
Section: Introductionmentioning
confidence: 97%